A Historical Perspective on the Development of β‐Adrenergic Blockers - Frishman, William H. (J Clin Hypertens (Greenwich), 2007)
The introduction of β‐adrenergic‐blocking drugs into clinical medicine in the early 1960s represented a major advance in pharmacotherapy. The use of these drugs highlighted the importance of the sympathetic nervous system in contributing to the pathophysiology of a wide variety of cardiovascular and noncardiovascular disorders. This article summarizes the history of β‐blocking agents and reviews the applications of this therapeutic class. These drugs may be useful as primary protection against cardiovascular morbidity and mortality in hypertensive patients and have proved to be beneficial in other cardiovascular conditions. Not all β‐blockers have the same mechanism of action and, among them, there are pharmacologic differences that may be of clinical importance.